PENGARUH MACAM JARAK TANAM JAJAR LEGOWO DAN DOSIS PUPUK ORGANIK KOTORAN AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI - Ana Amiroh; Nasrul Ilmi; Dian Eka Kusumawati (AGRORADIX : Jurnal Ilmu Pertanian, 2021)
tion. One of the efforts to evercome the problem of rice dependence is by adjusting the spacing and giving thr right dose of organic fertilizer. The purpose of this study was to determine the effect of orgaic fertilizer dosage and spacing on rice growth and production. This research was conducted in Solokuro Villlage, Solokuro Sub-ditrict, Lamongan Regency in April-June 2021. This research was conducted using a factorial randomized block design method consisting of two factors, namely types of organic fertilizers and spacing. The observed parameters observed were plant height, number of tillers, panicle length, wet grain weight and 1000 seeds wheught. From the results of research that has been carried out on the treatment of doses of organic chicken fertilizer doses of spacing on the growth and production of rice plants (Oryza sativa L.) it can be concluded that; There was an interaction with the observation of the number of tassels aged 75 day. There were significant differences in the single treatment of planting distance on the parameters of height observation of plants aged 21, 28, 35 and 42 hst, the number of tillers aged 14, 21 and 28 HST, and the number of tillers aged 42 HST and the number of panicles at the age of 68 and 82 HST, And there was no significant difference in the observation of plant height at 7 DAP, 14 DAP, the number of tillers at 7 DAP, the number of panicles at 61 DAP and 1000 seeds dry weight, wet grain weight and dry grain weight. And the best results were obtained in the treatment of 25 x 25 x 40 cm spacing and 10 tons/ha of chicken manure.